View-Dependent Displacement Mapping - Wang, Lifeng; Wang, Xi; Tong, Xin; Lin, Steve; Hu, Shimin; Guo, Baining; Shum, Harry (ACM Transactions on Graphics (TOG) - Proceedings of ACM SIGGRAPH 2003, 2003)
Significant visual effects arise from surface mesostructure, such as fine-scale shadowing, occlusion and silhouettes. To efficiently render its detailed appearance, we introduce a technique called iewdependent displacement mapping (VDM) that models surface displacements along the viewing direction. Unlike traditional displacement mapping, VDM allows for efficient rendering of selfshadows, occlusions and silhouettes without increasing the complexity of the underlying surface mesh. VDM is based on per-pixel processing, and with hardware acceleration it can render mesostructure with rich visual appearance in real time. CR Categories: I.3.3 [Computer Graphics]: Picture/Image Generation; I.3.7 [Computer Graphics]: Three-Dimensional Graphics and Realism.